PENGARUH PERUBAHAN TARIF PAJAK PENGHASILAN BADAN TERHADAP RETURN SAHAM DENGAN LIABILITAS PAJAK TANGGUHAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI (Periode 2008 – 2010) - Galih Rhendra Putra; Heru Tjaraka (InFestasi, 2016)
This research aimed to test whether there is the effect of changes in corporate income tax rate to return stock with deferred tax liabilities as an intervening variable. Changes in corporate income tax rates expected to have an indirect effect on stock returns. Variables used in this research include the change in the corporate tax rate as independent variables, stock returns as dependent variable and deferred tax liabilities as an intervening variable. The population used in this research were all manufacturing companies listing on the Stock Exchange in the period the change in corporate income tax rate is 2008-2010. Data were analyzed using path analysis technique to assess causal relationships between variables that have been set. The results of this research indicate that the phenomenon of corporate income tax rate changes have no significant effect either on the deferred tax liabilities and stock returns, while deferred tax liabilities had a positive effect on stock returns. Results of this research concluded that the deferred tax liabilities can not be a mediator or intervening variable between corporate income tax rate changes and stock returns.